Compute the length of the parametric curve
x=(t2−2)sint+2tcost
y=(2−t2)cost+2tsint
from t1=0 to t2=
I know that I need to square the derivatives, and then add them together, and square root them, and then integrate. Is there anyway to uncomplicate the terms before I start doing the derivative? As it stands, it looks like it will be unnecessarily complicated...
AH! Sorry, I copied the question down wrong...
Compute the length of the parametric curve
x=(t^2−2)sint+2t cost
y=(2−t^2)cost+2t sint
I don't know if that changes anything. Sorry again, I was in a hurry as I needed to get a 2000 word english essay done...